Mesh-covered (Roadsaver) stent as a new treatment modality for symptomatic or high-risk carotid stenosis - Machnik, Roman; Paluszek, Piotr; Tekieli, Łukasz; Dzierwa, Karolina; Maciejewski, Damian; Trystuła, Mariusz; Brzychczy, Andrzej; Banaszkiewicz, Krzysztof; Musiał, Robert; Pieniążek, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Prevention of periprocedural stroke has a crucial role in carotid artery stenting (CAS) procedures. Aim : To assess retrospectively 30-day safety and effectiveness of 41 procedures of internal and common carotid artery stenting using the Roadsaver double nitinol layer micromesh stent in 40 non-consecutive patients with symptomatic or high-risk carotid artery stenosis. Material and methods : The patients were men (n = 31) and women (n = 9); mean age was 67.8 ±7.9 years. Femoral access was used in 39 cases, whereas radial access was used in 2. Proximal (n = 27) or distal (n = 14) embolic neuroprotection was used. Results : The Roadsaver stents (nominal diameter 7, 8 or 9 mm, length 25 or 30 mm) were implanted successfully in all cases. One minor stroke occurred after common carotid artery intubation with a guiding catheter (before stent deployment) and one transient postprocedural ischemic attack (TIA) of the ipsilateral cerebral hemisphere was observed. Internal/common carotid artery stenosis severity was evaluated by duplex Doppler. Maximal peak systolic velocity (PSV) before CAS was in the range: 2.0–7.0 m/s, mean: 3.9 ±1.0 m/s, at 24–48 h after stenting mean PSV was 1.1 ±0.4 m/s (p < 0.05), and at 30 days 1.1 ±0.3 m/s (p < 0.05). Maximal end-diastolic velocity (EDV) was 0.85–3.5 m/s, mean 1.4 ±0.5 m/s, at 24–48 h after stenting mean EDV was 0.3 ±0.1 m/s (p < 0.05), and at 30 days 0.4 ±0.1 m/s (p < 0.05). No restenosis or thrombosis was observed. Angiographic stenosis decreased from 82.9 ±9.1% (range: 61–97%) to 19.3 ±7.3% (range: 0–34%) (p < 0.05). Conclusions : The CAS using the Roadsaver stent seems to be safe and effective. Further studies involving larger patient populations and longer follow-up are needed.